The Effect of Job Placement, Competency, Career Development, and Motivation on Employee Job Statisfaction at Badan Pusat Statistik Kabupaten Bogor - Fitria Erisa Suci; Subur Karyatun; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine and analyze the effect of job placement, competence, career development and motivation on employee job satisfaction at Badan Pusat Statistik Kabupaten Bogor. This type of research uses descriptive quantitative methods and inferensial analysis using primary data in the form of a closed questionnaire to 100 respondents, and model feasibility test, the regression equation is “Y = 1.426 + 0.315 X1 + 0.257 X2 + 0.162 X3 + 0.208 X4”. The results showed that job placement, competence,career development and motivation had a positive and significant effect on employee job satisfaction. A very significant variable is job placement (X1) with a significant level of 0.000. In an effort to increase employee job satisfaction, the Badan Pusat Statistik Kabupaten Bogor needs to pay attention and know what is the problem because it can be used as a basis for correcting weakness and maintaining effectiveness through good job placement, competence, career development and motivation.